Implementation of the kurikulum merdeka and challenges in instilling character in elementary schools - Syifa, Putri; Nazurty; Haryanto, Eddy (Jurnal Bidang Pendidikan Dasar, 2025)
The Merdeka Curriculum addresses educational challenges in Indonesia by offering flexible learning and emphasizing character development. SD Negeri 194/VI Tambang Emas I has adopted this curriculum to enhance learning quality and align students with the Profil Pelajar Pancasila. However, challenges remain, including teacher readiness, parental involvement, and limited infrastructure. This study uses a qualitative case study approach, collecting data through observations, interviews with teachers and students, and document analysis. Data were analyzed using reduction, presentation, and conclusion techniques to understand implementation challenges and opportunities. The findings show that while the curriculum's flexibility enhances project-based learning, its effectiveness is hindered by a lack of teacher training and administrative burdens. Additionally, low parental engagement and inadequate infrastructure remain significant barriers. To ensure successful implementation, practical teacher training, stronger school-parent communication, and improved facilities are essential. Strengthening these aspects will help optimize the curriculum’s benefits for students